APPLICATION OF THE NUMBERED HEADS TOGETHER LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN THE BASIC COMPETENCIES OF APPLYING OCCUPATIONAL SAFETY AND HEALTH AND ENVIRONMENTAL PROCEDURES (K3LH) - Salom Berkat Telaumbanua; Aprianus Telaumbanua; Arisman Telaumbanua; Envilwan Berkat Harefa; Adrianus Zega (Sean Institute, 2023)
This study aims to determine the learning process by using the Numbered Head Together (NHT) learning model in teaching at SMK Negeri 2 Gunungsitoli and to determine the improvement of student learning outcomes in the basic competencies of Application of Occupational Safety and Health and Environmental Procedures by using the Numbered Head Together (NHT) learning model at SMK Negeri 2 Gunungsitoli for the 2021/2022 academic year. This type of research is Classroom Action Research (PTK). The instruments used include: observation in the learning process (Teacher Respondents), observation sheets of student activeness in the learning process, student learning outcomes tests, interviews and documentation. This research was conducted in class X-DPIB even semester of SMK Negeri 2 Gunungsitoli in 2021/2022 with 14 students. The results of the study were obtained: (1) In cycle I (first) the average observation of teacher respondents in the learning process of the first meeting was 55% and the second meeting was 60% with an average percentage of 57.5%. The percentage of observations of students who were active in the learning process of the first meeting was 40.90% and the second meeting was 49.00% with an average percentage of 44.95%. The percentage of students who were not actively involved in the learning process of the first meeting was 51% and the second meeting was 59.1% with an average percentage of 57.5%. The average student learning outcomes were 64.04 with a percentage of completeness of 42.85% and a percentage of incompleteness of 58.00% (2) In cycle II (second) the percentage of observations of teacher respondents in the learning process of the first meeting was 80% and the second meeting was 87.5% with an average of 83.75%. The percentage of observations of students who were active in the learning process the first meeting was 77.5% and the second meeting was 83.5% with an average of 80.5%.. It is concluded that the application of the Numbered Head Together (NHT) learning model to improve student learning outcomes in the basic competencies of Applying Occupational and Environmental Health and Safety Procedures.